Ethnomedicinal Uses of Fabaceae Species for Respiratory Infections and Related Symptoms in the Limpopo Province, South Africa - Sebua Silas Semenya; Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2018)
Purpose: The present study investigated utilisation of Fabaceae species as herbal medicines for respiratory infections and related symptoms in the Limpopo Province, South Africa. Methods: Information on Fabaceae species used as herbal medicines against respiratory infections was gathered using semi-structured questionnaires during face-to-face interviews with 240 Pedi speaking traditional healers (THs) from May to July 2017. Voucher specimens of utilized plant species were collected and their identities and scientific names authenticated by a plant taxonomist at the University of Limpopo’s Larry Leach Herbarium. Results: Twenty-five plant species belonging to 16 genera were used by THs in treating 13 respiratory infections. Majority of the species (64.0%, n=16) were multi-used while 36.0% (n=9) treated a single condition each. Plants which showed the highest fidelity level (FL) scores included Acacia senegal (chronic cough=FL; 32.8, chest pain=FL; 32.8, tuberculosis=FL; 32.8), Dichrostachys cinerea (tuberculosis= FL; 100) and Acacia erioloba (pneumonia=FL; 92.7). These species were also characterized by high use value (UV) indices of 2.5, 0.82 and 0.58, respectively. Conclusion: Some of the plants recorded in this study are reported in literature to have potent biological activities against diverse pathogens which cause respiratory infections and perceived symptoms.